Discovery, Development, and Adoption of Medications to Treat Alcohol Use Disorder: Goals for the Phases of Medications Development. (17th May 2016) - Litten, Raye Z.; Falk, Daniel E.; Ryan, Megan L.; Fertig, Joanne B.
Abstract : For more than 25 years, advances have been made in developing medications to treat alcohol use disorder (AUD), highlighted by the U.S. Food and Drug Administration's approval of naltrexone (oral and long‐acting) and acamprosate. Despite this progress, more work remains to be done in this area because these medications, although effective for some people, do not work for everyone. A high priority for the National Institute on Alcohol Abuse and Alcohol is to put into place a solid infrastructure to aid in the development of medications that are more effective than those currently available and with few side effects. Medication development, especially for a disorder as complex as AUD, is challenging and involves multiple phases, including discovery of "druggable" targets, preclinical studies, human clinical trials, and the adoption and implementation of the new medication into mainstream medicine. A successful medications development program requires clearly established goals for each phase to ensure that a candidate compound is not trapped in one particular phase, a condition known as "the valley of death." In this article, the phases of medication development are described as they apply to AUD, and specific goals of each phase are identified for the next decade. In addition, several important crosscutting themes are outlined for each phase, all of which are essential for advancing medications development. These include identifying and validating screening models and druggable targets, making use of precision medicine, and establishing partnerships among key stakeholders. Our goal in writing this article is to provide a guide on medications development that will aid the alcohol research community in planning, testing, and developing medications for AUD. Abstract : A successful medications development program for the treatment of alcohol use disorder (AUD) requires clearly established goals for each phase of development to ensure that a candidate compound is not trapped in one particular phase. In this article, the phases of medication development are described as they apply to AUD, and specific goals of each phase are identified for the next decade. We hope this will aid the alcohol research community in planning, testing, and developing medications for AUD.